(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2023)
Background: Abdominal trauma is one of the most common causes of children’s death and fatal injury. Due to advances in technology, available facilities, and improved trauma transport, the management of trauma victims becomes earlier and easier in developed countries. In underdeveloped and developing countries, it is difficult as early recognition, timely reaching to health facilities, and management initiation become delayed. Objectives: This study was aimed at analyzing the mechanisms and causes, organ involvement, management, and outcome of childhood abdominal trauma in a tertiary centre in Bangladesh. Methods: This was a retrospective review of children from 0 – 12 years admitted to the department of Paediatric Surgery, Rajshahi Medical College Hospital, Bangladesh, with blunt and penetrating abdominal injuries from January 2020 to December 2021. Children with blunt abdominal trauma with either solid or hollow viscus injury and penetrating trauma with peritoneal breach and/or organ injury were included. Injuries only to the abdominal wall without organ injury were excluded. Results: 154 patients met the inclusion criteria with a 2.2:1 male-to-female ratio. The majority were 6 – 12 years of age (47.4%), most of them were presented with blunt trauma (142, 92.2%), and the leading cause of trauma was a road traffic accident (63.6%), which was followed by a fall from height (16.9%) and fall on a sharp object (6.5%). Out of 98 patients with road traffic accidents, only 16 (16.3%) were traumatized from traffic-traffic collisions, and the rest (83.7%) were injured during the crossing or running on the road. Commonly injured organ was the liver (52.6%), spleen (14.2%), and small intestine (9.7%). Most (70.1%) were treated conservatively, and 3 out of 4 died within 24 hours of admission. Conclusion: Road traffic accident was the most common cause of abdominal trauma, and the liver was the most commonly injured organ. Most of the victims were pedestrians. The cause is a lack of awareness and attendance to children and unsafe vehicles on the road. Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1&2): 28-32